Practical Ruby for System Administration - Ben-Hamou, Andre. (Apress : Imprint: Apress, 2007)
Ruby has set the world on fire, proving itself a serious challenger to Perl and Python in all spheres. In particular, more and more people are discovering that Ruby's flexibility, superb feature set, and gentle learning curve make it a natural choice for system administration tasks, from the humblest server to the largest enterprise deployment. Within the pages of Practical Ruby for System Administration, you'll learn the Ruby way to construct files, tap into clouds of data, build domain-specific languages, perform network traffic analysis, and more. Based on author André Ben Hamou's own experiences working as a system administrator, this book will help you pick up practical tips on Ruby coding style, learn how to analyze and improve script performance, and make use of no-nonsense advice on scripting workflow, including testing and documentation. Above all, you'll come to appreciate the sheer power of Ruby and the hundreds of benefits it offers for system administration. This book places equal emphasis on fundamental Ruby concepts as well as practical how-tos. It uses examples from other languages to ease the transition to Ruby. The book is concise, entertaining, and informative—unlike many books aimed at system administrators, which can be overly long and stodgy.